2009
DOI: 10.1299/jmmp.3.898
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Local Hydrogen Distribution Around Fatigue Crack Tip of a Type 304 Stainless Steel with Secondary Ion Mass Spectrometry and Hydrogen Micro-Print Technique

Abstract: In order to establish an appropriate method for measuring the local hydrogen content distribution around a fatigue crack tip in austenitic stainless steels, secondary ion mass spectrometry (SIMS) and the hydrogen micro-print technique (HMPT) were applied to a fatigue crack in a type 304 stainless steel fatigued in a hydrogen gas environment. The main results in this study are as follows. In the SIMS method, it is visualized that a high content of hydrogen exists in the plastic zone at a fatigue crack tip propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Their research findings indicated that hydrogen tends to segregate at grain boundaries, leading to an increased likelihood of intergranular fracture. Unfortunately, SIMS is prone to signal interference from the surrounding environment [17,18]. Over the past few years, scanning Kelvin probe force microscopy (SKPFM) has gained recognition as an effective and non-invasive technique for highresolution mapping of localized hydrogen distribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Their research findings indicated that hydrogen tends to segregate at grain boundaries, leading to an increased likelihood of intergranular fracture. Unfortunately, SIMS is prone to signal interference from the surrounding environment [17,18]. Over the past few years, scanning Kelvin probe force microscopy (SKPFM) has gained recognition as an effective and non-invasive technique for highresolution mapping of localized hydrogen distribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen embrittlement has been well accepted as one of the most severe steel degradation mechanisms [1][2][3][4]. There are several theories to illustrate hydrogen embrittlement in steel.…”
Section: Introductionmentioning
confidence: 99%
“…Chapter 2. Review on hydrogen diffusion modelling Ion Mass Spectrometry (SIMS) (Brass, Chene, & Boutry-Forveille, 1996;Mao & Li, 1998) and Micro-Print Technique (Kawamoto et al, 2009).…”
mentioning
confidence: 99%